CHARACTERISATION OF SOYBEAN RHIZOBIAL STRAINS FROM JAVA AND SUMATRA - Setiyo Hadi Waluyo; Tek An Lie; Leendert’t Mannetje; Willem M. de Vos (Indonesian Journal of Agricultural Science, 2005)
To get insight in the structure of soybean rhizobial population native to Indonesian soils, a thorough survey of the occurrence of the soybean rhizobia were conducted in several locations in Java and Sumatra. A total of 51 different isolates of rhizobial strains were characterised phenotypically based on their symbiotic properties, and genetically using amplified ribosomal DNA restriction analysis (ARDRA). Based on their nodulation capacity on both soybean and the native legume mungbean, these rhizobial strains could be divided into a group of 16 strains specific for soybean only and another group of 35 promiscuous strains that nodulated both leguminous plants. Based on ARDRA of PCRamplified 16S rDNA and 16S-23S rDNA spacer fragments, the rhizobial strains isolated from Java differed with those from Sumatra. Six Java isolates and only one Sumatra isolate were classified as Bradyrhizobium japonicum and these similar to that of B. japonicum strain USDA 110. All these B. japonicum strains were highly specific for soybean. One isolate from Java showed a rather unique position. The remaining strains from Java (20), which were symbiotically promiscuous strains, were clustered in another group. This group and another group containing most Sumatra isolates were distinct from B. japonicum USDA 110 and therefore it is tempting to speculate that these represent indigenous soybean rhizobial bacteria. Application of agricultural practices, such as enhancement of rhizobial population, to increase soybean production is still essential and noteworthy in Sumatra.